Every team needs a coach: Training for interprofessional clinical placements. Issue 5 (2nd September 2016) - Grymonpre, Ruby; Bowman, Susan; Rippin-Sisler, Cathy; Klaasen, Kathleen; Bapuji, Sunita B.; Norrie, Ola; Metge, Colleen
ABSTRACT: Despite growing awareness of the benefits of interprofessional education and interprofessional collaboration (IPC), understanding how teams successfully transition to IPC is limited. Student exposure to interprofessional teams fosters the learners' integration and application of classroom-based interprofessional theory to practice. A further benefit might be reinforcing the value of IPC to members of the mentoring team and strengthening their IPC. The research question for this study was: Does training in IPC and clinical team facilitation and mentorship of pre-licensure learners during interprofessional clinical placements improve the mentoring teams' collaborative working relationships compared to control teams? Statistical analyses included repeated time analysis multivariate analysis of variance (MANOVA). Teams on four clinical units participated in the project. Impact on intervention teams pre- versus post-interprofessional clinical placement was modest with only the Cost of Team score of the Attitudes Towards Healthcare Team Scale improving relative to controls ( p  = 0.059) although reflective evaluations by intervention team members noted many perceived benefits of interprofessional clinical placements. The significantly higher group scores for control teams (geriatric and palliative care) on three of four subscales of the Assessment of Interprofessional Team Collaboration Scale underscore our need to better understand the unique features within geriatric and palliative care settings that foster superior IPC and to recognise that the transition to IPC likely requires a more diverse intervention than the interprofessional clinical placement experience implemented in this study. More recently, it is encouraging to see the development of innovative tools that use an evidence-based, multi-dimensional approach to support teams in their transition to IPC.